1980
DOI: 10.1128/jvi.35.1.184-193.1980
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the simian virus 40 genome into cellular DNA in temperature-sensitive (N) and temperature-insensitive (A) transformants of 3T3 rat and Chinese hamster lung cells

Abstract: phenol and once with chloroform-isoamyl alcohol (24: 1, vol/vol). The extracts were then dialyzed, incubated with 0.1 mg of RNase A (Boehringer) per ml, incubated again with proteinase K (0.1 mg/ml), reextracted, and dialyzed, as described by Botchan et al. (4). The molecular weight of the DNA was checked by agarose gel electrophoresis. Restriction enzymes, digestion, and agarose gels. Cellular DNA (25 ,Lg) was digested for 2 to 5 h with restriction enzymes by using the incubation media specified by New Englan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1981
1981
1984
1984

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Transformation of cells by simian virus 40 (SV40) is stabilized by integration of all or part of the viral genome into that of the cell. Previous studies (4,5,7,14), in which the sizes of restriction endonuclease fragments bearing SV40 DNA were determined by Southern blot analysis of DNA extracted from a variety of rat and mouse transformed cell lines, have shown that integration of SV40 DNA is nonspecific with respect to the position on the SV40 genome at which viral DNA is linked to cellular DNA. These studies also suggested that SV40 DNA does not integrate at specific sites in the cellular genome.…”
mentioning
confidence: 99%
“…Transformation of cells by simian virus 40 (SV40) is stabilized by integration of all or part of the viral genome into that of the cell. Previous studies (4,5,7,14), in which the sizes of restriction endonuclease fragments bearing SV40 DNA were determined by Southern blot analysis of DNA extracted from a variety of rat and mouse transformed cell lines, have shown that integration of SV40 DNA is nonspecific with respect to the position on the SV40 genome at which viral DNA is linked to cellular DNA. These studies also suggested that SV40 DNA does not integrate at specific sites in the cellular genome.…”
mentioning
confidence: 99%
“…So far, most analyses on the arrangement of Py and simian virus 40 DNA in transformed cells indicated that integration is unspecific with respect to both viral and cellular DNA sequences (2,6,7,17,25,27,48). However, similar integration patterns have been found for some independently isolated rat cell lines transformed by simian virus 40 (8,34). The synthesis of the 61-kDal truncated IT and the specificity of integration observed in our study could be due to a particular nucleotide sequence, presumably located between 7 and 8.9 map units on the viral genome.…”
Section: Discussionmentioning
confidence: 83%
“…Fisher rat 3T3 cell lines that were transformed by a temperature-sensitive mutant of SV40, but that were temperature insensitive and that contained SV40 sequences at one (FR3T3 A12) or a few (FR3T3 A24 and FR3T3 A84) sites (3,9), were grown at the nonpermissive temperature, and flat revertants were selected. (No attempt was made to determine precisely the frequency of reversion, but calculating from the number of cells used and the number of flat revertants obtained, the frequency was roughly 1 in 107.…”
Section: Resultsmentioning
confidence: 99%
“…The cell lines and blotting techniques have been described previously (3,9), except that the partial acid hydrolysis procedure of Wahl et al (13) was added. The selection for flat revertants was carried out at 40°C precisely as described by Steinberg et al (11).…”
Section: Methodsmentioning
confidence: 99%